Flash‐sintering of magnesium aluminate spinel (MgAl2O4) ceramics. Issue 2 (31st October 2016) - Yoshida, Hidehiro; Biswas, Papiya; Johnson, Roy; Mohan, Mantravadi Krishna
Abstract: The sintering behavior of commercially available MgAl2 O4 spinel was investigated under DC electric field in a range of 0 and 1000 V/cm. Flash‐sintering results in densification close to theoretical density at 1410°C under the DC field of 1000 V/cm, in comparison to the higher sintering temperature of 1650°C in case of conventional sintering. It was observed that the fields less than 750 V/cm had no significant effect on the densification behavior. An abrupt increase in power dissipation was observed corresponding to the occurrence of the flash event. A significant enhancement in grain size was observed in case of flash‐sintered dense spinel samples. The gradual increase in the specimen conductivity observed in the electric field‐assisted sintering (FAST) regime led to Joule heating within the specimen. The increased specimen temperature triggered further increment of current and Joule heating, resulting in the immediate densification.